Comparing the Efficacy of IV Ibuprofen and Ketorolac in the Management of Postoperative Pain Following Arthroscopic Knee Surgery. A Randomized Double-Blind Active Comparator Pilot Study - Uribe, Alberto A.; Arbona, Fernando L.; Flanigan, David C.; Kaeding, Christopher C.; Palettas, Marilly; Bergese, Sergio D. (Frontiers in Surgery, 2018)
Introduction: Acute postoperative pain following knee arthroscopy is common in orthopedic surgeries. Managing pain postoperatively combines usage of opioids and non-steroidal anti-inflammatory drugs. The aim of this clinical study was to assess the efficacy of two different analgesic treatment regimens: intravenous (IV) ibuprofen and IV ketorolac for the treatment of postoperative pain pertaining arthroscopic knee surgery. Methods: This was a single center, randomized, double-blind, parallel, active comparator clinical pilot study. Subjects were randomized to receive either IV ibuprofen, administered as two 800 mg doses or IV ketorolac, administered as a single 30 mg dose. Subjects in the ibuprofen group received 800 mg of IV ibuprofen within 2 hours prior to surgery and a repeated second dose four hours after the initial dose if they had not been discharged. Subjects in the ketorolac group received IV ketorolac 30 mg at the end of surgery, as per the manufacturer’s recommendations. Pain assessments and opioid consumption data were collected up to 24 hours postoperatively. Results: 51 subjects received intervention in this study. Visual analog scale (VAS) pain scores in the ibuprofen group demonstrated a greater than two-fold reduction in the ibuprofen group at all measured time points while at rest and in motion, with statistical significance from PACU arrival up to 90 minutes after surgery. There was a significant reduction in the need for postoperative opioid medication for pain in the ibuprofen group (n=10, 52.63%) versus the ketorolac group (n=26, 86.67%). Additionally, the total amount of narcotic consumption in the ibuprofen group, compared to the ketorolac group was significantly reduced (5.39 ± 6.02 mg vs 20.58 ± 15.45 mg oral morphine, p<0.0001). There were no significant differences between these groups. No adverse events directly related to study medications occurred. Conclusion: The findings of this pilot study indicate that, compared to postoperative IV ketorolac 30 mg, the administration of preemptive IV ibuprofen 800 mg reduces both postoperative pain at rest and opioid consumption within the first 24 hours postoperatively.